The answer is the first expression 8(4 + 2 )
32 + 16 = 48 and so does the first expression
x-y=4
How do you get the y alone?
The answer is y = x-4.
Step-by-step explanation:
⇒ -y = 4-x
⇒ y = x-4
6.59+(−7.8)−(−2.41)=
On evaluating the decimal expression given by →
6.59 + (− 7.8) − ( − 2.41), we get 1.2
A decimal is a number that consists of a whole and a fractional part. For example - 9.3, 5.4, 9.8 etc.
Given is the following expression -
6.59 + (− 7.8) − ( − 2.41)
The given decimal expression is -
6.59 + (− 7.8) − ( − 2.41)
Simplifying it -
6.59 - 7.8 + 2.41
6.59 - 5.39
1.2
Therefore, on evaluating the decimal expression given by →
6.59 + (− 7.8) − ( − 2.41), we get 1.2.
To solve more questions on Evaluating expressions, visit the link below-
#SPJ2
Answer:
1,2
Step-by-step explanation:
6,59-7,8+2,41=1,2